1998
DOI: 10.1007/s002469900256
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Pediatric Cardiology: State of the Art and Future Directions

Abstract: Although the interventional pediatric cardiology began in the early 1950s, it was not until the mid-1980s that a full spectrum of transcatheter interventions in children could be undertaken including balloon atrial septostomy which has been in usage since 1966. Enormous developments have occurred even from the mid-1980s to date. In this review, current state-of-the-art for each broad area of therapeutic catheterization is presented. A large variety of lesions could be opened-up or closed, as the case may be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 149 publications
0
11
0
2
Order By: Relevance
“…We proposed the concept of using stents for this purpose while discussing state of the art and future directions in interventional pediatric cardiology in 1998 [284]. The very following year Atz et al [281] reported stent placement across the atrial septum after trans-atrial needle puncture in a neonate with hypoplastic left heart syndrome and intact atrial septum.…”
Section: Atrial Septal Stentsmentioning
confidence: 99%
“…We proposed the concept of using stents for this purpose while discussing state of the art and future directions in interventional pediatric cardiology in 1998 [284]. The very following year Atz et al [281] reported stent placement across the atrial septum after trans-atrial needle puncture in a neonate with hypoplastic left heart syndrome and intact atrial septum.…”
Section: Atrial Septal Stentsmentioning
confidence: 99%
“…When the pulmonary valve annulus is too large to dilate with a single balloon, valvuloplasty with simultaneous inflation of two balloons across the pulmonary valve annulus is recommended. Immediate, short-term and long-term results ( Figure 4) are good; although long-term results are limited (Rao et al 1998). Given the success with balloon pulmonary valvuloplasty, surgery is reserved for unsuccessful balloon cases, mostly for cases with supravalvar PS, severe valve annular hypoplasia and dysplastic pulmonary valves.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Indeed, at the present time balloon pulmonary valvuloplasty is treatment of choice. The indications for intervention are similar to those prescribed for surgery: a peak-to-peak systolic pressure gradient > 50 mmHg across the pulmonary valve with a normal cardiac index (Rao 1988, Rao 1989b, Rao 1998. Detailed description of the procedure of balloon valvuloplasty and the results of such a procedure are beyond the scope of this chapter; the reader is referred elsewhere for these details (Rao 2007a, Rao 2007b.…”
Section: Managementmentioning
confidence: 99%
“…There are a large number of other congenital, acquired or postsurgical stenotic lesions which can be effectively treated with balloon therapy [2,3,5,6,19,20] and include stenotic pulmonary valve in tetralogy of Fallot or other single ventricle lesions, post-surgical aortic recoarctation, branch pulmonary artery stenosis, mitral valve stenosis, some forms of Takyasu's arteritis, heterograft or homograft valve/conduit stenosis, supravalvar stenosis following arterial switch procedure, baffle stenosis following Mustard or Senning procedure for transposition of the great arteries, vena caval obstructive lesions, stenosed Blalock-Taussig shunts, obstructed collateral vessels in pulmonary atresia patients. Discussion of these lesions is beyond the scope of this presentation.…”
Section: Other Usesmentioning
confidence: 99%
“…Balloon dilatation techniques were then extended to relieve obstructive lesions of the aorta,pulmonary valve, aortic valve, mitral valve,subaortic membrane, branch pulmonary artery stenosis, stenoticbioprosthetic valves and other obstructive vascular lesions. Extensive review of the techniques and results may be found in our previous publications on this subject [1][2][3][4][5][6][7][8]. …”
mentioning
confidence: 99%